MUSLIMS SCHOOLGIRLS' IDENTITY AND PARTICIPATION IN SCHOOL-BASED PHYSICAL EDUCATION IN ENGLAND - António Gomes Ferreira; José António Moreira (University of Banja Luka, Faculty of physical education and sport, 2012)
This article draws from an ethnographic case study of a group of Muslim schoolgirls at two schools in England. It examines the issues surrounding their religious and ethnic identity and whether this conflicts with participation in school-based Physical Education (PE). Social Identity Theory underpinned the study, focusing the research and interpretation of empirical data gathered over a period of twenty months, mainly by in-depth semi-structured interviews to explicate the PE experiences through employment of a qualitative methodology.The social categories of ethnicity and religion play a key part in shaping the identity of Muslim schoolgirls. The girls perceive PE as a subject, which allows for freedoms not found elsewhere in the curriculum and they recognise the importance of physical activity. The study confirms the findings of previous research, which found that issues of kit, fasting during Ramadan and extra-curricular activities posed problems for Muslim pupils; these are features, which are especially compounded when teachers are not aware of the issues.The findings demonstrated the exclusionary nature of traditional physical education settings. The experiences of pupils were more reliant upon the quality of individual teachers. Multi-cultural and racism-awareness courses appear to be indispensable for a better understanding of the pupils, and making them available to all teachers, regardless of their hierarchical standing, can be advantageous.